Isatuximab plus carfilzomib and dexamethasone in relapsed multiple myeloma patients with high-risk cytogenetics: IKEMA subgroup analysis - Spicka, Ivan; Moreau, Philippe; Martin, Thomas G; Facon, Thierry; Martinez, Gracia; Oriol, Albert; Koh, Youngil; Lim, Andrew; Mikala, Gabor; Rosiñol, Laura; Yağci, Münci; Cavo, Michele; et al. (European journal of haematology, 2022)
INTRODUCTION: The presence of high-risk chromosomal abnormalities [t(4;14), del(17p), and t(14;16)] has been linked with inferior outcomes in patients with multiple myeloma (MM). A prespecified interim analysis of the Phase 3 IKEMA study (NCT03275285) demonstrated that isatuximab (Isa) + carfilzomib (K) and dexamethasone (d; Isa-Kd) significantly improved progression-free survival (PFS) versus Kd in patients with relapsed MM. This prespecified subgroup analysis of IKEMA examined efficacy and safety in patients with high-risk cytogenetics. METHODS: High-risk cytogenetics was assessed by central laboratory and patients were classified as high risk if abnormalities were present in ≥1 of the following: del(17p): 50% cutoff; t(4;14), and/or t(14;16): 30% cutoff. RESULTS: Of the randomized patients, 23.5% (Isa-Kd) and 25.2% (Kd) had ≥1 high-risk chromosomal abnormality. A PFS benefit was seen in favor of Isa-Kd for patients with standard-risk (HR 0.440; 95% CI 0.266-0.728) and high-risk cytogenetics (HR 0.724; 95% CI 0.361-1.451). Grade ≥3 treatment-emergent adverse events (TEAEs) were more common with Isa-Kd (85.7%) versus Kd (63.3%) in patients with high-risk cytogenetics; however, the incidence of serious TEAEs (64.3% vs. 66.7%) was similar. CONCLUSIONS: Isa-Kd is a new treatment option for the difficult-to-treat subgroup of patients with relapsed MM and high-risk cytogenetics.
Keywords: Oligopeptides; protokoly protinádorové kombinované chemoterapie; humanizované monoklonální protilátky; lidé; Multiple Myeloma; Antibodies, Monoclonal, Humanized; oligopeptidy; mnohočetný myelom; dexamethason; Dexamethasone; Antineoplastic Combined Chemotherapy Protocols; Humans